From Home-Based Kitchens to Competitive Markets: Strengthening Culinary Msme Capacity Through Practical Training - Johan Pratama Siahainenia; Gladys Greselda Gosal; Hari Minantyo; Kristian Agung Nugraha; Devi Rahnjen Wijayadne (Plakat : Jurnal Pelayanan Kepada Masyarakat, 2026)
This study is grounded in the persistent challenges faced by culinary heritage-based small and medium-sized enterprises (SMEs), in which strong product authenticity is often undermined by inconsistent cooking quality and unprofessional packaging, thereby limiting market competitiveness in contemporary contexts. The objective of this research is to examine the effectiveness of an integrated development strategy that combines cooking skill enhancement and packaging design innovation in revitalizing culinary heritage enterprises, employing a mixed-method approach with a dominant qualitative-descriptive design involving participatory observation, in-depth interviews, visual documentation, expert taste evaluation, and pre– and post–comparative assessment of selected enterprises participating in an intensive capacity-building program. The findings demonstrate significant improvements in cooking-skill mastery, product consistency, food-safety compliance, packaging aesthetics, storytelling effectiveness, and overall market readiness, collectively contributing to increased perceived value, expanded market access, and short-term sales growth. Furthermore, the results confirm that modernization practices such as recipe standardization, quality control, and professional packaging do not diminish culinary authenticity but instead reinforce its sustainability and reproducibility. The implications of this study suggest that culinary heritage revitalization initiatives should adopt a holistic intervention model that integrates product quality enhancement with visual storytelling, supported by policy frameworks that facilitate continuous training, innovation support, and market linkage to ensure long-term economic viability and cultural preservation.Penelitian ini dilatarbelakangi oleh tantangan yang terus dihadapi oleh usaha kecil dan menengah (UKM) berbasis warisan kuliner, di mana autentisitas produk yang kuat sering kali tereduksi oleh ketidakkonsistenan kualitas masakan serta penyajian kemasan yang kurang profesional, sehingga membatasi daya saing di konteks pasar modern. Tujuan penelitian ini adalah untuk mengkaji efektivitas strategi pengembangan terpadu yang menggabungkan peningkatan keterampilan memasak dan inovasi desain kemasan dalam merevitalisasi usaha kuliner berbasis warisan, dengan menggunakan pendekatan metode campuran yang didominasi oleh desain deskriptif kualitatif melalui observasi partisipatif, wawancara mendalam, dokumentasi visual, evaluasi cita rasa oleh ahli, serta penilaian komparatif sebelum dan sesudah pada pelaku usaha yang mengikuti program peningkatan kapasitas secara intensif. Hasil penelitian menunjukkan adanya peningkatan signifikan dalam penguasaan keterampilan memasak, konsistensi produk, kepatuhan terhadap standar keamanan pangan, estetika kemasan, efektivitas storytelling, serta kesiapan pasar secara keseluruhan, yang secara kolektif berkontribusi pada peningkatan nilai persepsi, perluasan akses pasar, dan pertumbuhan penjualan jangka pendek. Selain itu, temuan ini menegaskan bahwa praktik modernisasi seperti standarisasi resep, pengendalian kualitas, dan kemasan profesional tidak mengurangi autentisitas kuliner, melainkan justru memperkuat keberlanjutan dan reprodusibilitasnya. Implikasi dari penelitian ini menunjukkan bahwa inisiatif revitalisasi warisan kuliner perlu mengadopsi model intervensi holistik yang mengintegrasikan peningkatan kualitas produk dengan storytelling visual, serta didukung oleh kerangka kebijakan yang memfasilitasi pelatihan berkelanjutan, dukungan inovasi, dan keterhubungan pasar guna menjamin keberlanjutan ekonomi jangka panjang serta pelestarian budaya.